Formation of children's human capital in Kenya: The role of teachers, private schools and the family - Wamalwa, Fredrick Masinde (School of Economics, 2018)
In this thesis, we contribute to knowledge about the human capital formation of children in Kenya in three interrelated essays. We focus on Kenya due to the declining learning outcomes the country is experiencing, in the wake of increasing public spending in the education sector. The first essay examines the effect of teacher subject knowledge, pedagogical skill, teacher effective instruction time and teacher classroom practices on grade 4 language and maths test scores. Our results show that a one standard deviation increase in the teacher's knowledge in language (maths) increases student test scores by 0.075 (0.126) of a standard deviation in language (maths). An additional hour of teacher effective instruction time increases student achievement by 0.051 and 0.059 score standard deviations in language and maths, respectively. The second essay estimates the size of the effect of private school attendance on literacy (language) and numeracy (maths) skill acquisition among children drawn from lower primary grades (grades 2-4) in Kenya. Using a household survey data, we apply different estimation techniques (OLS, fixed effects and propensity score matching) to deal with the potential endogeneity of school choice. We find positive and significant effects of private school attendance on both language and maths achievements across all the estimation techniques. For instance, the household fixed effects yield a private school premium of 0.13 to 0.21 score standard deviation in maths and language, respectively. The third essay examines the effect of the gender and order of birth of a child on intra-household investments in, and educational outcomes of, children in Kenya. We measure the intra-household education investment in children by the household's decision to enrol a child in a private school. We define educational outcomes by two variables: completed years of education and relative grade progression. We control for the potential endogeneity of child's gender, birth order, family size and household level unobservables using household fixed effects model. We find no female advantage in terms of private school enrolment. However, there is a consistent female advantage in terms of completed years of education and relative grade progression. We find significant negative birth order effects on private school enrolment, completed years of education and relative grade progression.